Reforming the World : The Creation of America's Moral Empire - Tyrrell, Ian R. (Book collections on Project MUSE., 2010)
Reforming the World offers a sophisticated account of how and why, in the late nineteenth and early twentieth centuries, American missionaries and moral reformers undertook work abroad at an unprecedented rate and scale. Looking at various organizations such as the Young Men's Christian Association and the Student Volunteer Movement for Foreign Missions, Ian Tyrrell describes the influence that the export of American values had back home, and explores the methods and networks used by reformers to fashion a global and nonterritorial empire. He follows the transnational American response to internal pressures, the European colonies, and dynamic changes in global society. Examining the cultural context of American expansionism from the 1870s to the 1920s, Tyrrell provides a new interpretation of Christian and evangelical missionary work, and he addresses America's use of "soft power." He describes evangelical reform's influence on American colonial and diplomatic policy, emphasizes the limits of that impact, and documents the often idiosyncratic personal histories, aspirations, and cultural heritage of moral reformers such as Margaret and Mary Leitch, Louis Klopsch, Clara Barton, and Ida Wells. The book illustrates that moral reform influenced the United States as much as it did the colonial and quasi-colonial peoples Americans came in contact with, and shaped the architecture of American dealings with the larger world of empires through to the era of Woodrow Wilson. Investigating the wide-reaching and diverse influence of evangelical reform movements, Reforming the World establishes how transnational organizing played a vital role in America's political and economic expansion.